2021
DOI: 10.1016/j.xkme.2021.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Patient Awareness of CKD: A Systematic Review and Meta-analysis of Patient-Oriented Questions and Study Setting

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 50 publications
(163 reference statements)
1
33
0
Order By: Relevance
“…This has been an area of debate in the nephrology field for quite some time [16]. Prevalence of CKD awareness among patients differs when asked with different terms (eg, "kidney problem," "chronic kidney disease," "weak or failing kidneys") [17][18][19]. Weak or failing kidneys is currently used in the most widely cited metric for CKD awareness in the United States, implying that low awareness is at least in part the result of semantics.…”
Section: Principal Findings and Comparison With Prior Workmentioning
confidence: 99%
“…This has been an area of debate in the nephrology field for quite some time [16]. Prevalence of CKD awareness among patients differs when asked with different terms (eg, "kidney problem," "chronic kidney disease," "weak or failing kidneys") [17][18][19]. Weak or failing kidneys is currently used in the most widely cited metric for CKD awareness in the United States, implying that low awareness is at least in part the result of semantics.…”
Section: Principal Findings and Comparison With Prior Workmentioning
confidence: 99%
“…There is also little knowledge among US physicians regarding drug dosage in patients with a history of CKD (27). According to studies conducted in the United States and Australia, knowledge of one's own disease is also very low among patients who suffer from CKD, which poses even greater challenges for the physician who provides care for them (28)(29)(30). Such a physician should communicate to the patient, in a clear and accessible way, the principles to be followed in their everyday life with the new disease.…”
Section: Figurementioning
confidence: 99%
“…Previous studies also suggest that , 50% of individuals with CKD are aware of their condition, and the range of awareness may vary on the basis of the nomenclature used to describe kidney disease, which lacks uniformity. 19,20 Analysis of National Health and Nutrition Examination Survey data from 2005 to 2012 demonstrated that awareness is lower in the general population, compared with studies conducted in hospital, primary care, and nephrology clinics, with only 7.4% of individuals in the United States with CKD were aware of their disease. 21 This article presents the results of an analysis of Behavioral Risk Factor Surveillance System (BRFSS) data on the prevalence of self-reported kidney disease and related risk factors among older LGBT1 adults compared with their heterosexual peers, with additional context from existing literature.…”
Section: Introductionmentioning
confidence: 99%